Chronic social stress disrupts the intracellular redistribution of brain hexokinase 3 induced by shifts in peripheral glucose levels - Michael A. van der Kooij; Liliana Rojas-Charry; Maryam Givehchi; Christina Wolf; Diones Bueno; Sabine Arndt; Stefan Tenzer; Lorenzo Mattioni; Giulia Treccani; Annika Hasch; Michael J. Schmeisser; Caterina Vianello; et al. (Journal of Molecular Medicine, 2022)
Chronic stress has the potential to impair health and may increase the vulnerability for psychiatric disorders. Emerging evidence suggests that specific neurometabolic dysfunctions play a role herein. In mice, chronic social defeat (CSD) stress reduces cerebral glucose uptake despite hyperglycemia. We hypothesized that this metabolic decoupling would be reflected by changes in contact sites between mitochondria and the endoplasmic reticulum, important intracellular nutrient sensors, and signaling hubs. We thus analyzed the proteome of their biochemical counterparts, mitochondria-associated membranes (MAMs) from whole brain tissue obtained from CSD and control mice. This revealed a lack of the glucose-metabolizing enzyme hexokinase 3 (HK3) in MAMs from CSD mice. In controls, HK3 protein abundance in MAMs and also in striatal synaptosomes correlated positively with peripheral blood glucose levels, but this connection was lost in CSD. We conclude that the ability of HK3 to traffic to sites of need, such as MAMs or synapses, is abolished upon CSD and surmise that this contributes to a cellular dysfunction instigated by chronic stress. Key messages Chronic social defeat (CSD) alters brain glucose metabolism CSD depletes hexokinase 3 (HK3) from mitochondria-associated membranes (MAMs) CSD results in loss of positive correlation between blood glucose and HK3 in MAMs and synaptosomes

An improved method for precise genome editing in zebrafish using CRISPR-Cas9 technique - Eugene V. Gasanov; Justyna Jędrychowska; Michal Pastor; Malgorzata Wiweger; Axel Methner; Vladimir P. Korzh (Molecular Biology Reports, 2021)
Current methods of CRISPR-Cas9-mediated site-specific mutagenesis create deletions and small insertions at the target site which are repaired by imprecise non-homologous end-joining. Targeting of the Cas9 nuclease relies on a short guide RNA (gRNA) corresponding to the genome sequence approximately at the intended site of intervention. We here propose an improved version of CRISPR-Cas9 genome editing that relies on two complementary guide RNAs instead of one. Two guide RNAs delimit the intervention site and allow the precise deletion of several nucleotides at the target site. As proof of concept, we generated heterozygous deletion mutants of the kcng4b , gdap1 , and ghitm genes in the zebrafish Danio rerio using this method. A further analysis by high-resolution DNA melting demonstrated a high efficiency and a low background of unpredicted mutations. The use of two complementary gRNAs improves CRISPR-Cas9 specificity and allows the creation of predictable and precise mutations in the genome of D. rerio .

Abnormalities of synaptic mitochondria in autism spectrum disorder and related neurodevelopmental disorders - Liliana Rojas-Charry; Leonardo Nardi; Axel Methner; Michael J. Schmeisser (Journal of Molecular Medicine, 2021)
Autism spectrum disorder (ASD) is a neurodevelopmental condition primarily characterized by an impairment of social interaction combined with the occurrence of repetitive behaviors. ASD starts in childhood and prevails across the lifespan. The variability of its clinical presentation renders early diagnosis difficult. Mutations in synaptic genes and alterations of mitochondrial functions are considered important underlying pathogenic factors, but it is obvious that we are far from a comprehensive understanding of ASD pathophysiology. At the synapse, mitochondria perform diverse functions, which are clearly not limited to their classical role as energy providers. Here, we review the current knowledge about mitochondria at the synapse and summarize the mitochondrial disturbances found in mouse models of ASD and other ASD-related neurodevelopmental disorders, like DiGeorge syndrome, Rett syndrome, Tuberous sclerosis complex, and Down syndrome.

New Probucol Analogues Inhibit Ferroptosis, Improve Mitochondrial Parameters, and Induce Glutathione Peroxidase in HT22 Cells - Diones Caeran Bueno; Rômulo Faria Santos Canto; Viviane de Souza; Rafaela Rafognatto Andreguetti; Flávio Augusto Rocha Barbosa; Aline Aita Naime; Partha Narayan Dey; Verena Wüllner; Mark William Lopes; Antônio Luiz Braga; Axel Methner; Marcelo Farina (Molecular Neurobiology, 2020)

Bax inhibitor-1 deficiency leads to obesity by increasing Ca2+-dependent insulin secretion - Koenraad Philippaert; Michael Roden; Dmitrij Lisak; Diones Bueno; Tomas Jelenik; Konstantin Radyushkin; Teresa Schacht; Margot Mesuere; Verena Wüllner; Ann-Kathrin Herrmann; Jan Baumgart; Rudi Vennekens; et al. (Journal of Molecular Medicine, 2020)
Transmembrane BAX inhibitor motif containing 6 (TMBIM6), also known as Bax inhibitor-1, is an evolutionarily conserved protein involved in endoplasmic reticulum (ER) function. TMBIM6 is an ER Ca 2+ leak channel and its deficiency enhances susceptibility to ER stress due to inhibition of the ER stress sensor IRE1α. It was previously shown that TMBIM6 overexpression improves glucose metabolism and that TMBIM6 knockout mice develop obesity. We here examined the metabolic alterations underlying the obese phenotype and subjected TMBIM6 knockout mice to indirect calorimetry and euglycemic-hyperinsulinemic tests with stable isotope dilution to gauge tissue-specific insulin sensitivity. This demonstrated no changes in heat production, food intake, activity or hepatic and peripheral insulin sensitivity. TMBIM6 knockout mice, however, featured a higher glucose-stimulated insulin secretion in vivo as assessed by the hyperglycemic clamp test and hepatic steatosis. This coincided with profound changes in glucose-mediated Ca 2+ regulation in isolated pancreatic β cells and increased levels of IRE1α levels but no differences in downstream effects of IRE1α like increased Xbp1 mRNA splicing or Ire1-dependent decay of insulin mRNA in the pancreas. We therefore conclude that lack of TMBIM6 does not affect insulin sensitivity but leads to hyperinsulinemia, which serves to explain the weight gain. TMBIM6-mediated metabolic alterations are mainly caused by its role as a Ca 2+ release channel in the ER. Key messages TMBIM6 −/− leads to obesity and hepatic steatosis. Food intake and energy expenditure are not changed in TMBIM6 −/− mice. No changes in insulin resistance in TMBIM6 −/− mice. Increased insulin secretion caused by altered calcium dynamics in β cells.

Presenilin-1 Delta E9 Mutant Induces STIM1-Driven Store-Operated Calcium Channel Hyperactivation in Hippocampal Neurons - Maria Ryazantseva; Anna Goncharova; Kseniia Skobeleva; Maksim Erokhin; Axel Methner; Pavel Georgiev; Elena Kaznacheyeva (Molecular Neurobiology, 2018)

Regulators of mitochondrial Ca2+ homeostasis in cerebral ischemia - Michael K. E. Schäfer; Annika Pfeiffer; Martin Jaeckel; Alireza Pouya; Amalia M. Dolga; Axel Methner (Cell and Tissue Research, 2014)

Genetic shift of env V3 loop viral sequences in patients with HIV-associated neurocognitive disorder during antiretroviral therapy - Christian Eggers; Oliver Müller; Ingo Thordsen; Michael Schreiber; Axel Methner (Journal of NeuroVirology, 2013)